Carry that weight: coastal foraging and transport of marine resources during the South African Middle Stone Age - Dusseldorp, G. L.; Langejans, G. H. J. (Southern African Humanities, 2013)
The influence of transport and processing behaviour on the composition of archaeological assemblages is often poorly understood. We study the influence of changing transport distances, due to Late Pleistocene sea-level fluctuations, on the representation of marine resources at Middle Stone Age sites in South Africa. We show that the representation of some marine resources does not decrease proportionally with increased transport distance. This suggests that the organisation of foraging behaviour changed as sea levels fluctuated. We develop a model of the organisation of Middle Stone Age coastal foraging strategies, explaining the exploitation of marine resources as a function of fluctuations in the productivity of terrestrial relative to marine resources.